2017
DOI: 10.1371/journal.pone.0178004
|View full text |Cite|
|
Sign up to set email alerts
|

Measurement of macular structure-function relationships using spectral domain-optical coherence tomography (SD-OCT) and pattern electroretinograms (PERG)

Abstract: BackgroundRetinal ganglion cell (RGC) death is a common cause of loss of vision during glaucoma. Pattern electroretinogram (PERG) is an objective measure of the central retinal function that correlates with macular GCL thickness. The aim of this study is to determine possible relationships between the N95 amplitude of pattern electroretinogram (PERGamp) and macular ganglion cell/inner plexiform layer thickness (GCIPLT).Methods and findingsThis was a retrospective and comparative study including 74 glaucoma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
2
10
2
Order By: Relevance
“…The mean deviation for their study groups was –1.89, –0.85, and 0.14, respectively. The results of the study by Park et al 15 coincide with our results as they had an average VF MD of –0.97, –3.23, and –12.2 for their three groups: normal, early glaucoma, and advanced glaucoma, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean deviation for their study groups was –1.89, –0.85, and 0.14, respectively. The results of the study by Park et al 15 coincide with our results as they had an average VF MD of –0.97, –3.23, and –12.2 for their three groups: normal, early glaucoma, and advanced glaucoma, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…They concluded that pERG amplitude was significantly correlated with GCIPLT in early glaucoma patients, while visual field test results showed no correlation with GCIPLT or pERG. 15…”
Section: Discussionmentioning
confidence: 99%
“…These results are in general agreement with an earlier report by Park et al ., who did not find a connection between macular GCIPL thickness and VF loss 9 . In that study, a significant association between GCIPL thickness and VF damage was found only in patients with advanced glaucoma 9 . In the present report, patients with early stage glaucoma were included: Mean MD was determined to be −2.8 dB in the PFS group and −2.6 dB in the PNS group.…”
Section: Discussionmentioning
confidence: 84%
“…PERGs are known to generally measure electrical activity upon central stimulation of the macula (typically <15° stimulus field) 3,9 . Recently, several types of PERG were developed in which the visual angle was extended to 44° horizontally, which is similar to the horizontal visual angle (52°) examined by 24-2 standard automated perimetry (SAP 24-2) 5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Foveal threshold (FT), MD, total deviation (TD), and pattern standard deviation (PSD) were evaluated. TD was divided into three areas (central, midperipheral, and peripheral areas) without Mariotte blind spot ( Fig 1 ) based on the important location of the VF for the quality of vision such as reading and mobility [ 11 ], which were compared by average value for each area. Then, we compared the difference in these parameters among EDOF group, bifocal group and monofocal group.…”
Section: Methodsmentioning
confidence: 99%